Mineralogy and Permeability of Gas and Oil Dolomite Reservoirs of the Zechstein Main Dolomite Basin in the Lubiatów Deposit (Poland) - Ewa Krogulec; Katarzyna Sawicka; Sebastian Zabłocki; Ewa Falkowska (Energies, 2020)
Permeability characterizes the ability of rocks to store and transport natural gas, crude oil and reservoir fluids. Permeability heterogeneity of reservoir rocks, including dolomites, results from overlapping geological and physicochemical processes. The permeability study of gas-bearing dolomites was carried out on the Lubiatów hydrocarbon deposit (Poland), located at the Ca2 carbonate platform toe-of-slope, which is a prospective area for hydrocarbon exploration in Europe. Due to the complicated rock textures and overlapping alteration processes, including secondary crystallization or dissolution of minerals, the permeability of the deposit is variable. Studies of dolomites from a depth of 3242–3380 m show high mineralogical diversity; the percentage of dolomite ranges from 79% to 95% with a variable content of other minerals: anhydrite, gypsum, quartz, fluorite, plagioclase and clay minerals. The porosity variability ranges from 4.69% to 31.21%, depending on the measurement method used. The mean permeability value is 35.27 mD, with a variation range of 0.9 to 135.6 mD. There is neither change in permeability with depth and mineral composition, nor a direct relationship between porosity and permeability.